Nanoparticle-electrode collision processes: the underpotential deposition of thallium on silver nanoparticles in aqueous solution. - Zhou, Y; Rees, N; Compton, R (2011)
The electrochemistry of collisions between metal nanoparticles (NPs) and electrode surfaces has been of recent interest with the development of anodic particle coulometry as a characterisation method. For the first time the underpotential deposition of metal ions from solution onto metal nanoparticles during collisions between the NPs and an inert electrode is reported.